EFEKTIVITAS EKSTRAK BUAH MENGKUDU (Morinda citrifolia) TERHADAP KADAR MDA SEBAGAI PEMICU ATEROSKLEROSIS - Iin Desmiany Duri; Ari Suwondo; Suhartono - - (Dian Nuswantoro Semarang, 2020)
Morinda cirifolia (Noni) has been used widely as a complementary and alternative therapy in many countries owing to ita potent. There were so many study concluded that oxidative stress increased in atherosclerosis. Oxidative stress can be defined as an imbalance between prooxidants and antioxidants, because antioxidants could not quench over production of prooxidants. This study investigated the effect of mengkudu extract (Morinda citrifolia linn) as antioxidant on malondialdehyde (MDA) level (prooxidant marker) in egg yolk induced rats. This experimental study had been carried out to 25 rats with 150-200 gram weight which divided into three group of four rats each, i.e. negative control, positive control egg yolk induced, and the group was treated by egg yolk induced which followed by dosis variai mengkudu extract oral (26mg, 52 mg and 104 mg/WB/day) for 28 days. The result was analyzed by using one way Anova with confidence interval 95%. There were significantly different in groups (p<0,05). The conclusion is mengkudu extract has capability to quench MDA level in rats Rattus norvegicus strain wistar.Keywords: mengkudu extract , MDA level